Mortality among children in Basrah - Omran S Habib; Suham A Warid (The Medical Journal of Basrah University, 2015)
Background: Childhood mortality is a sensitive indicator of the health and socioeconomic status of population. Differential figures across populations and/or over time suggest variation in the quality of health, health care and standard of living. During the last three decades, all indicators of childhood mortality showed declining trend but a great variation does exist between developed and developing countries with some countries, mostly African have the highest rates. Objectives: The present study was conducted to estimate the mortality rate among children aged less than 15 years in Basrah over a 6-year period and to identify the major causes of childhood mortality. Methods: A retrospective, record-based study using all official records of deaths among children during the years 2008-2013. Results: The study demonstrated that overall childhood mortality rate for the years (2008-2013) in Basrah governorate was within the international pattern with a tendency towards lower figures among various countries. Infant mortality (22.4/1000 live births) is still high as compared to many countries. Regarding the sex distribution an excess of male specific mortality rate is seen. Mortality among male children was 3.26/1000 males and 2.85/1000 female children. No explanation is verifiable but excess exposure to risk factors, such as outdoor activities could be implicated. The five leading causes of childhood death; perinatal causes, bacterial infections, congenital anomalies, accidents and diseases of the respiratory system accounted for 72.8% of all registered childhood deaths in Basrah governorate during the years.2008-2013. Most of these conditions are amenable to prevention. Conclusions: A substantial proportion of deaths among children were related to causes of death that are amenable to prevention. Key words: Childhood mortality, Basrah, Retrospective, Death